Pengaruh Cita Rasa dan Kualitas Layanan terhadap Loyalitas Pelanggan Mie Gacoan Sidoarjo di Platform Gofood melalui Kepuasan Pelanggan Sebagai Variabel Mediasi - Faizatul Isnaini; Muhafidhah Novie; Jeziano Rizkita Boyas; Edita Rachma Kamila (Riwayat: Educational Journal of History and Humanities, 2025)
This research aims to analyze the influence of taste and service quality on Mie Gacoan customer loyalty in Sidoarjo with customer satisfaction as a mediating variable on the GoFood platform. The quantitative method was used with a purposive sampling technique, involving 190 respondents who were regular customers. Data collection was carried out through questionnaires and analyzed using SmartPLS 3.0. The research results show that taste and service quality have a significant influence on customer loyalty. The better the taste and quality of the service provided, the higher the customer satisfaction which ultimately increases customer loyalty. Customer satisfaction is proven to mediate the relationship between these two variables and customer loyalty. This research emphasizes the importance of maintaining consistent taste quality and improving service quality to increase customer satisfaction, which ultimately contributes to customer loyalty. Culinary business owners, especially those in online delivery services, need to better maintain and increase customer loyalty.